PHARMACOECONOMIC STUDY OF LENVIMA (LENVATINIB) IN ADVANCED PROGRESSIVE RADIO IODINE REFRACTORY DIFFERENTIATED THYROID CANCER IN THE RUSSIAN FEDERATION - M. Yu. Frolov; V. A. Rogov (IRBIS LLC, 2016)
Objective: to conduct a pharmacoeconomic analysis of lenvatinib (Lenvima) in advanced progressive radio iodine refractory differentiated thyroid cancer in the Russian Federation.Methods. Cost-effectiveness ratio (CER) and budget impact analysis (BIA) were performed. All calculations were made in the MS Excel model. CER compared lenvatinib 24 mg/daily, sorafenib 800 mg/daily and Other chemotherapies mix. BIA compared two scenarios: 1) common practice consisting of sorafenib and Other chemotherapies mix; 2) new practice where lenvatinib is used in 6.25% patients. Costs of drugs, visits to oncologist and hospitalization were calculated both in CER and BIA. Time horizon was 2 years for CER and 5 years for BIA.Results. Lenvatinib is a new highly effective target drug for the monotherapy of the radioiodine refractory differentiated thyroid cancer. Lenvatinib significantly increases progression free survival, thus providing in the proposed model, 1628 additional years of life for patients per 5 years. Additional costs at the same time constitute 5 213 900 000 rub. (670.5 to 1184.3 million rubles per year). Calculated unit lenvatinib efficiency stands at 64.95% less than that of the comparisons targeted drug (sorafenib).